The Branding of Padang City: How Does It Affect The City Image and Tourist Visit Decision? - Heru Aulia Azman; Monica Tuti Suryani; Ares Albirru Amsal (AMAR (Andalas Management Review), 2019)
Padang has widely known as the tourism destination in Indonesia. This city is the capital of West Sumatera Province which win three World Halal Tourism Award categories in 2016; World's Best Halal Culinary Destination, World's Best Halal Destination and Halal World's Best Tour Operator. This study aims to determine the effect of Padang’s city branding (Presence, Place, potential, Pulse, People, Pre-requisite) towards its city image (cognitive, affective, conative) and tourist visit decision. Moreover, city image is also placed to be intervening variable between city branding and tourist visit decision. Based on the tourist data collected by survey (200 samples), structural equation modeling using Smart PLS 3.0 and Sobel Test were employed to test the research model. The findings indicate that the relationship in purposed model are significant. For researchers this study provides a basis for further development of city banding of Padang. For government and destination marketing organization (DMO), understanding the key construct is crucial to increase visitors and better perceived city image.